1178. Sustained Vaccine Effectiveness Against Influenza-Associated Hospitalization in Children: Evidence from the New Vaccine Surveillance Network, 2015-2016 Through 2019-2020. (4th December 2021) - Sahni, Leila C; Naioti, Eric A; Olson, Samantha M; Campbell, Angela P; Michaels, Marian G; Williams, John V; Allen Staat, Mary; Schlaudecker, Elizabeth P; Halasa, Natasha B; Halasa, Natasha B; Stewart, Laura S; Englund, Janet A; et al.
Abstract: Background: Adult studies have demonstrated intra-season declines in influenza vaccine effectiveness (VE) with increasing time since vaccination; however, data in children are limited. Methods: We conducted a prospective, test-negative study of children ages 6 months through 17 years hospitalized with acute respiratory illness at 7 pediatric medical centers each season in the New Vaccine Surveillance Network during the 2015-2016 through 2019-2020 influenza seasons. Cases were children with an influenza-positive molecular test; controls were influenza-negative children. Controls were matched to cases by illness onset date using 3:1 nearest neighbor matching. We estimated VE [100% x (1 – odds ratio)] by comparing the odds of receipt of ≥ 1 dose of influenza vaccine ≥ 14 days before the onset of illness that resulted in hospitalization among influenza-positive children to influenza-negative children. Changes in VE over time between vaccination date and illness onset date during each season were estimated using multivariable logistic regression models. Results: Of 8, 430 hospitalized children (4, 781 [57%] male; median age 2.4 years), 4, 653 (55%) received ≥ 1 dose of influenza vaccine. On average, 48% and 85% of children were vaccinated by the end of October and December, respectively. Influenza-positive cases (n=1, 000; 12%) were less likely to be vaccinated than influenza-negative controls (39% vs. 61%, p< 0.001) and overall VE against hospitalization was 53% (95% CI: 46%, 60%). Pooling data across 5 seasons, the odds of any influenza-associated hospitalization increased 0.96% (95% CI: -0.76%, 2.71%) per week with a corresponding weekly decrease in VE of 0.45% (p=0.275). Odds of hospitalization with time since vaccination increased 0.66% (95% CI: -0.76%, 2.71%) per week in children ≤ 8 years (n=3, 084) and 2.16% (95% CI: -1.68%, 6.15%) per week in children 9-17 years (n=771). No significant differences were observed by virus subtype or lineage. Figure 1. Declines in influenza VE over time from 2015-2016 through 2019-2020, overall (a) and by age group (b: ≤ 8 years; c: 9-17 years) Conclusion: We observed minimal intra-season declines in VE against influenza-associated hospitalization in U.S. children. Vaccination following Advisory Committee on Immunization Practices guidelines and current timing of vaccine receipt is the best strategy for prevention of influenza-associated hospitalization in children. Disclosures: Marian G. Michaels, MD, MPH, Viracor (Grant/Research Support, performs assay for research study no financial support) John V. Williams, MD, GlaxoSmithKline (Advisor or Review Panel member, Independent Data Monitoring Committee)Quidel (Advisor or Review Panel member, Scientific Advisory Board) Elizabeth P. Schlaudecker, MD, MPH, Pfizer (Grant/Research Support)Sanofi Pasteur (Advisor or Review Panel member) Natasha B. Halasa, MD, MPH, Genentech (Other Financial or Material Support, I receive an honorarium for lectures - it's a education grant, supported by genetech)Quidel (Grant/Research Support, Other Financial or Material Support, Donation of supplies/kits)Sanofi (Grant/Research Support, Other Financial or Material Support, HAI/NAI testing) Natasha B. Halasa, MD, MPH, Genentech (Individual(s) Involved: Self): I receive an honorarium for lectures - it's a education grant, supported by genetech, Other Financial or Material Support, Other Financial or Material Support; Sanofi (Individual(s) Involved: Self): Grant/Research Support, Research Grant or Support Janet A. Englund, MD, AstraZeneca (Consultant, Grant/Research Support)GlaxoSmithKline (Research Grant or Support)Meissa Vaccines (Consultant)Pfizer (Research Grant or Support)Sanofi Pasteur (Consultant)Teva Pharmaceuticals (Consultant) Christopher J. Harrison, MD, GSK (Grant/Research Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support) Flor M. Munoz, MD, Biocryst (Scientific Research Study Investigator)Gilead (Scientific Research Study Investigator)Meissa (Other Financial or Material Support, DSMB)Moderna (Scientific Research Study Investigator, Other Financial or Material Support, DSMB)Pfizer (Scientific Research Study Investigator, Other Financial or Material Support, DSMB)Virometix (Other Financial or Material Support, DSMB)